"The Pill Line Is Longer Than the Chow Line": The Impact of Incarceration on Prisoners and Their Families. (March 2018) - DeHart, Dana; Shapiro, Cheri; Clone, Stephanie
Incarceration removes individuals from their families and their communities, increasing the potential for disrupted relationships, community fragmentation, and burden on service systems. Based on focus groups with 38 male and 39 female inmates and interviews with 21 family members, this study identifies specific impacts of incarceration on prisoners and their families. Findings include prisoners' and families' perceptions of incarceration's impact on their communication, health, mental health, finances, and involvement with community supports such as friends, church groups, and human services. Implications for research, practice, and policy are discussed.